2020
DOI: 10.1038/s41598-019-57123-1
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Network Pattern Identification by Community Modelling

Abstract: Temporal network mining tasks are usually hard problems. This is because we need to face not only a large amount of data but also its non-stationary nature. In this paper, we propose a method for temporal network pattern representation and pattern change detection following the reductionist approach. The main idea is to model each stable (durable) state of a given temporal network as a community in a sampled static network and the temporal state change is represented by the transition from one community to ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…An alternative approach to using the dissipation index can include temporal community detection [40]; however, this method is not necessarily suitable for the data-scarce regime with only two time points considered in this work. The indication that the post-hoc analysis of communities is more suitable for analysis was also recently demonstrated when studying fire events in a portion of the Amazon basin [41].…”
Section: Dissipation Between Two Time Pointsmentioning
confidence: 82%
“…An alternative approach to using the dissipation index can include temporal community detection [40]; however, this method is not necessarily suitable for the data-scarce regime with only two time points considered in this work. The indication that the post-hoc analysis of communities is more suitable for analysis was also recently demonstrated when studying fire events in a portion of the Amazon basin [41].…”
Section: Dissipation Between Two Time Pointsmentioning
confidence: 82%
“…The authors showed the effectivity of the proposed method in some artificial datasets, and in a case study analyzing wildfire events from the same temporal Chronnets dataset [2,13]. As a result, they also detected two central communities in the Amazon region, each one corresponding to different periods of the year: the south-hemisphere winter season, with a high tendency of fires, and the south-hemisphere summer season, with a low frequency of fires [14]. However, these communities represent the global state of the wildfire system in the Amazon basin, not the micro spatialtemporal particularities or patterns into the microregions.…”
Section: Related Workmentioning
confidence: 92%
“…In this work, we aim to analyze the temporal information stored on the wildfire dataset by using temporal chronnets. Our analysis differs from previous works [2,13,14] once we seek to validate the results of the temporal community detection methods when modeling the wildfires, mainly concerning its spatial incidence and extension. Our methodology can reveal where and how often specific fire event patterns occur over the years.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Xubo et al [139] proposed a block-based method for detecting community structure from temporal networks, whose data can change or evolve over time. The method employs a reduction strategy using sampling.…”
Section: B Dynamic Clustering Categories and Methods 1) Using Auxiliary Update Clustering Category A: Block-based Clustering Methodsmentioning
confidence: 99%